Cold Chain Strategies for Seaports - Bob Castelein; Harry Geerlings; Ron Van Duin (European Journal of Transport and Infrastructure Research, 2020)
The refrigerated (‘reefer’) container market and cold logistics chains creates opportunities as well as challenges for seaports. This high-value market grows rapidly, but places stringent demands on seaports’ logistics processes, infrastructure, and energy provision. This study addresses the question how port authorities address the challenges and in this dynamic market environment. While previous research has outlined developments in port governance paradigms and the strategic scope of port authorities, the academic literature still lacks a comprehensive understanding of the policy options available to port authorities to respond to arising challenges and opportunities. To provide this missing understanding, this study presents a new dataset of policies, implemented by world’s 50 largest container ports, addressing reefer transportation and cold chain logistics. Policy measures are classified according to content, goals and scope. The findings from this worldwide comparative analysis illustrate that port authorities often pursue policies extending far beyond their traditional ‘landlord’ responsibility. Most commonly still, the scope of port policy is limited to the port cluster, where ports (co)-invest in or aim for cluster formation around cold stores. When a port extends its strategic scope towards its foreland or hinterland, this is usually aligned with policy goals formulated at higher levels of governance, such as modal shift goals or the development of domestic post-harvest distribution systems. There is however little evidence of coherent and comprehensive cold chain strategies, addressing the logistics, marketing, technology, and sustainability dimensions. The paper outlines the general tenets such a strategy should contain as a consideration for policymakers.